2019
DOI: 10.3390/genes10090648
|View full text |Cite
|
Sign up to set email alerts
|

Eukaryote Genes Are More Likely than Prokaryote Genes to Be Composites

Abstract: The formation of new genes by combining parts of existing genes is an important evolutionary process. Remodelled genes, which we call composites, have been investigated in many species, however, their distribution across all of life is still unknown. We set out to examine the extent to which genomes from cells and mobile genetic elements contain composite genes. We identify composite genes as those that show partial homology to at least two unrelated component genes. In order to identify composite and componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…Protein fusions comprise at least 4% of the monoPGT superfamily, the remaining sequences being small and large monoPGTs (38% and 47%, respectively) and sequences which could not be categorized into families based on sequence alone (11%). A recent comprehensive study of fusion event frequency across genomes from all three domains of life has revealed that, although there is a wide range among the 90 genomes characterized, on average, bacterial genomes include 14% fusion proteins (46). Additionally, the frequency of fusion proteins is higher for metabolic enzymes, possibly supporting shuttling of pathway intermediates.…”
Section: Discussionmentioning
confidence: 99%
“…Protein fusions comprise at least 4% of the monoPGT superfamily, the remaining sequences being small and large monoPGTs (38% and 47%, respectively) and sequences which could not be categorized into families based on sequence alone (11%). A recent comprehensive study of fusion event frequency across genomes from all three domains of life has revealed that, although there is a wide range among the 90 genomes characterized, on average, bacterial genomes include 14% fusion proteins (46). Additionally, the frequency of fusion proteins is higher for metabolic enzymes, possibly supporting shuttling of pathway intermediates.…”
Section: Discussionmentioning
confidence: 99%